PENGGUNAAN GAYA BAHASA IKLAN SKINCARE PADA APLIKASI TIKTOK TERHADAP KEPUTUSAN PEMBELIAN DAN RELEVANSINYA DALAM PEMBELAJARAN KELAS VIII - Shifa Putri Awaliyah; Leli Nisfi Setiana (STKIP Subang, 2025)
The use of persuasive language in advertisements, especially in skincare productadvertisements on social media. This study aims to analyze the influence ofpersuasive language style in skincare advertisements on the purchasing decisionsof grade VIII junior high school students and their understanding of advertisingtexts in the context of learning Indonesian. Specifically, this study investigates howadvertising language style influences purchasing decisions, identifies the mosteffective types of language styles, and analyzes the relationship between studentsunderstanding of advertising text material and the advertisements they encounteron social media. This study uses a qualitative descriptive approach to gain an in-depth understanding of the phenomenon.The results show that the use of persuasive language style in skincareadvertisements has a significant influence on students purchasing decisions. Inaddition, this study identifies several types of language styles that are effective inattracting students attention and encouraging their purchasing interest. This studyalso reveals a relationship between students understanding of advertising textmaterial in class and their ability to interpret advertisements they encounter onsocial media. This study provides insight into the role of advertising language stylein shaping adolescent consumer behavior and its implications for the developmentof Indonesian language learning materials that are more contextual and relevant tostudents lives.